2008
DOI: 10.1007/s12011-008-8136-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Zinc, Copper, Copper/Zinc Ratio, and Activity of Carbonic Anhydrase in Equine Piroplasmosis

Abstract: We have determined the plasma concentrations of copper, zinc, copper/zinc ratio, and carbonic anhydrase activity in horses infected with Babesia equi. The study was conducted in 14 horses with the disease and 10 healthy animals that served as controls. The infection was confirmed by the clinical manifestations of the disease and by Giemsa staining of thin blood smears showing the parasites inside red blood cells. The horses with piroplasmosis had lower plasma levels of zinc, elevated copper, and increased acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The raising level of Cu is in connection with the level of ceruloplasmin such as observed in acute phase reactant (31). Also, similar results reported by Dedes et al (6) who was showed that equine piroplasmosis result in decreased plasma Zn level and increased Cu level. Furthermore, our recorded corroborate the opinion of (32) who reported that Hepatozoon canis caused an increased in serum Cu level and a decreased in Zn level.…”
Section: Trace Elements Estimationsupporting
confidence: 86%
See 1 more Smart Citation
“…The raising level of Cu is in connection with the level of ceruloplasmin such as observed in acute phase reactant (31). Also, similar results reported by Dedes et al (6) who was showed that equine piroplasmosis result in decreased plasma Zn level and increased Cu level. Furthermore, our recorded corroborate the opinion of (32) who reported that Hepatozoon canis caused an increased in serum Cu level and a decreased in Zn level.…”
Section: Trace Elements Estimationsupporting
confidence: 86%
“…Notwithstanding constituting an animal wellness issue, the parasitosis is a wellspring of financial misfortune for the meat business (1,5). There are several of studies demonstrating the relationship of trace elements with parasitic diseases (6,7). Some infectious diseases or chronic inflammation leads alteration in the level of trace elements but the reason is unknown yet and it needs more study (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Equine piroplasmosis (EP) is a tick-borne disease of all wild and domestic equids caused by the intraerythrocytic protozoan parasites Babesia caballi and Theileria equi (formerly Babesia equi), which may be observed separately or together (2,13,15). Since it has harmful effects on the health and thus the performance of equids, EP is considered as a serious threat.…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…EP is known to be manifested in three stages: acute, latent, and subclinical. Horses infected with Theileria equi have more severe clinical signs than those with Babesia caballi (2). The disease can be diagnosed by indirect immunefluorescent antibody test (IFAT), enzyme-linked immunoassays (ELISA), and polymerase chain reaction (PCR), as well as Giemsa-stained blood smears (2,7).…”
Section: Praca Oryginalnamentioning
confidence: 99%
See 1 more Smart Citation